The FTSE-British Olympic Association Initiative: A resource dependence perspective - Morrow, S.; Robinson, L. (Sport Management Review, 2013)
The Financial Times Stock Exchange (FTSE)-British Olympic Association (BOA) Initiative, a partnership scheme initiated in 2007 between a number of FTSE 100 companies and Olympic National Governing Bodies (NGBs) in the UK, seeks to improve the effectiveness of the Olympic NGBs delivery and subsequent performance through the provision of support in-kind from the corporate partner. The paper uses resource dependency theory to analyse the partnerships within the Initiative, focusing primarily on the operation and benefits of those partnerships from the perspective of the Olympic NGBs. Despite being the less powerful party in the partnership, the NGBs are able to use the partnerships to acquire critical resources. While the benefits received by the companies are softer and more social in nature, nevertheless they demonstrate mutual dependency between the partners. This knowledge provides an incentive for NGBs to engage in co-optation and constraint activities as a way to strengthen the dependency relationships and protect their position.